ANALISIS COST-BENEFIT PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY PROGRAM BOGASARI MITRA CARD SURABAYA - Wahyu Irawaty; Dianne Frisko (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2008)
One of the activities that company should do to maintain its sustainability nowadays is concern about society and environment by doing corporate social responsibility (CSR) activities. By doing CSR, company has shown their responsibility to all stakeholders aligned with the willingness to create sustainability development. Company could use varied tools to asses their CSR activities in order to evaluate their CSR implementation. This research is aimed to analyze cost and benefit of one CSR progame of PT. ISM Tbk Bogasari Flour Mills, by using Socio-Economic Impact to evaluate its progamme.